Life Style Modification Among Diabetic Patients (Journal of Dhaka Medical College, 2017)
Lifestyle modifications have key role in the management of diabetes. Awareness about the changes in lifestyle can play a vital role in the management of diabetes. There is a need of health education programs for diabetics and general population. As the diabetes is a slow progressive disease which causes target organ damage if not control. Study shows that controlled diabetics has also risk of target organ damage. Managing a diabetic patient needs to be combination of diet, discipline and drugs. Only drugs is given by the physician but the other two control parameter like diet and discipline is done by the patient himself. Life style modification can bring this two factor under control. Here we have studied 100 diabetic patient with following results.J Dhaka Medical College, Vol. 25, No.1, April, 2016, Page 46-52